Removal Ciprofloxacin Through Adsorption-Photocatalyst Properties of CaBi4Ti4O15 - Prasetyo, Anton; Saputra, Bima Ardi; Aeni, Siti Qurotul; Hikmah, Nurul (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
CaBi4Ti4O15 is one of the four-layer Aurivillius compound family and reported having photocatalytic properties. In this research, we synthesized CaBi4Ti4O15 by molten salt method, and then the reducing ciprofloxacin concentration ability by adsortion-photocatalysis process was studied. The diffractogram sample showed that CaBi₄Ti₄O₁₅ was successfully synthesized with no additional peaks detected which indicates the absence of impurities compound. The micrograph results showed that CaBi4Ti4O15 has a plate-like morphology with an average particle size of 150 μm. UV-Vis DRS results showed a bandgap energy of 3.148 eV (394.16 nm). The adsorption test showed that the ciprofloxacin concentration decreased 17.61% in 30 minutes. Meanwhile, the adsorption-photocatalyst test results showed that CaBi4Ti4O15 reduced the concentration of Ciprofloxacin at around 35% for 90 minutes.